Experimental Analysis of a Hybrid-Configured Battery Thermal Management System Using Paraffin Oil and Fan - Muhammad Firdaus Jauhari; Sairaji Sairaji; Ary Hewu Hawino; Zaky Abdillah; Bambang Sudarmanta; Mohammad Khoirul Effendi; Kristian Ismail (Universitas Muhammadiyah Magelang, 2025)
The study investigates the effectiveness of a Battery Thermal Management System (BTMS) using a hybrid configuration of paraffin oil and fan cooling. The research employs a comparative test method to evaluate the BTMS's potential in managing the thermal conditions of lithium-ion batteries, commonly used in electric vehicles. The study is conducted under three configurations: hybrid cooling with paraffin oil and fan, passive cooling with paraffin oil, and no cooling system. The ambient and liquid temperatures are measured, alongside battery voltage changes over a 60-minute period. The results indicate that the hybrid cooling system effectively maintains lower battery temperatures compared to passive and no cooling systems. Specifically, the hybrid system achieves an average ambient temperature of 33.344Â°C and a paraffin oil temperature of 32.982Â°C, demonstrating its superior cooling capability. The study concludes that the hybrid BTMS can significantly enhance battery performance and longevity by maintaining optimal temperature conditions, thus offering a viable solution for improving the efficiency and safety of electric vehicle batteries. This research has implications for the development of more effective thermal management systems in electric vehicles, potentially leading to increased adoption and improved sustainability in the automotive industry.